Parent-related factors on the early onset of romantic relationship among students of selected high schools in Quezon City - Del Valle, Maria Janina Regina D.; Oleta, Theresa Ann C.; Hizon, Evalyn G. (Quezon City UP College of Home Economics, 2012)
High school students' perceptions on three (3) parent related factors in relation to the early7 onset of romantic relationships were examined. The parent-related factors being pertained to are the following: (1) aspects of interparental conflict namely frequency, intensity, constancy and resolution, (2) maternal attachment and (3) paternal attachment. Sixty (60) 1st and 2nd year respondents from two (2) co-educational public high schools in Quezon City were randomly chosen to participate in answering the survey questionnaire. Then, respondents were divided into two groups namely the control group and the research group. The control group respondents are those who have never been involved in a romantic relationship, while the research group respondents are those who had been involved or were involved in a romantic relationship during the study. From the respondents who agreed to be interviewed, twenty-four (24) respondents were randomly selected for a 15-minute recorded face-to-face interview. Chi-Square Test and Analysis of Variance (ANOVA) were utilized to analyze the results from the Likert-type scales in the survey questionnaire. Meanwhile, interview responses were categorized into themes using Thematic Tables. Data from the survey questionnaire revealed that the average onset of romantic relationship was twelve (12) years old. Both the research and control groups identified "to have an inspiration" as the top reason for high school students' involvement in a romantic relationship. The Chi-square Test showed that the reason, "to see how attractive I am" was the only distinct characteristic of the research group from the control group. This reason is in consonance with one of the tasks indicated in Havighurst's Developmental Tasks Theory. Based on the ANOVA, only the mean responses of the control group and research group for the frequency aspect of interparental conflict had a significant difference. Moreover, interview responses on maternal and paternal attachment showed that research group respondents had both secure maternal and paternal attachments. The researchers concluded that among the parent-related factors, only the frequency aspect of interparental conflict, as well as the source of respondents on both maternal and paternal attachment, were the independent variables which seem to be promoting the research group respondents' early involvement in romantic relationships.
Thesis (BSFLCD)--University of the Philippines.
Keywords: Parent and teenager -- Philippines